Effect of germination on total phenolic, tannin and phytic acid contents in soy bean and peanut - Megat Radzi, Megat Rusydi; Azlan, Azrina (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Legume is a plant in the family of Fabacae or Leguminosae that rich in protein, carbohydrate, dietary fibre, and minerals. Germination of legume causes some important changes in the biochemical and a nutritional characteristic of the legumes that may be beneficial to human's health and nutritional status. This study was carried out to determine the effect of germination on total phenolic, tannin and phytic acid contents of soy beans and peanut. The process of germination was carried out by soaking legumes in water for 6 hours, followed by germinating them in wet muslin cloth for 48 hours. After germination, samples were dried and stored in refrigerator before analysis. Total phenolic, tannin and phytic acid were determined spectrophotometrically. Total phenolic contents were decreased significantly (p<0.05) in germinated peanut and soy bean while significant decreased (p<0.05) of tannin content was found in germinated peanut. Phytic acid content was decreased significantly (p<0.05) in germinated soy bean. Germination reduced total phenolic, tannin and phytic acid contents more in peanut compared to soy bean sample. The decreased in total phenolic, tannin and phytic acid content was due to enzymatic changes during germination period in seeds. Germinated beans can be incorporated with wheat-based food product such as bread or pasta to improve nutrition content.